DEVELOPING STUDENTS' CREATIVE POTENTIAL THROUGH INTEGRATED LESSONS - Yahyaeva Umida Sharifovna (Web of Journals Publishing, 2025)
The article examines the role of integrated lessons in developing students’ creative potential from both theoretical and practical perspectives. It highlights how interdisciplinary integration enhances learners’ ability to think systematically, generate original ideas, and approach problem-solving with flexibility and innovation. Within the research framework, a pedagogical model of integrated teaching was designed, criteria for assessing creativity were refined, and experimental tests were conducted to validate the effectiveness of the proposed approach. The findings demonstrate that integrated lessons significantly contribute to the development of students’ creative competencies and foster a learning environment that promotes intellectual independence, analytical thinking, and creative expression.
Keywords: Integrated lessons; interdisciplinary integration; creative potential; creativity assessment; pedagogical model; innovative education; student competencies